Sistem Pembiayaan Mitraguna Berkah pada PT Bank Syariah Indonesia Kcp Medan Setia Budi - Sisca Pratiwi Tbn (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Financing and activity of a sharia bank in disbursing funds to parties other than banks based on sharia principles. Raise the money What the World Bank has to offer helps meet people's needs. Fund distribution in the form of financing is carried out in good faith. Transferred from the owner of the funds to the user. One of them is Doctor And retirement. The purpose of this discussion is to find out how the system works. Mitraguna Berkah Financing Funding, further requirements for Submission of Mitraguna Blessing Financing, and Constraints and solutions in the financing process Mitraguna Berkah. Syariah Indonesia is Mitraguna Berkah with components - Cooperation agreements and components to conclude my agreement to take action at Bank Syariah Indonesia Kcp. Medan Setia Budi Namely with Bank Syariah Indonesia The process of distributing funds to companies or agencies, then to employees. Furthermore, there are requirements for the financing system of Bank Syariah Indonesia Mitraguna Berkah. Keywords: disbursing funds, financing, sharia bank